2004
DOI: 10.1017/s0031182003004736
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii major surface antigen (SAG1): in vitro analysis of host cell binding

Abstract: Article:Robinson, S.A., Smith, J.E. and Millner, P.A. (2004) SUMMARYPrevious studies have indicated that SAG1, the major surface molecule of the protozoan parasite Toxoplasma gondii,isan important attachment ligand for the host cell. However, the research data that supports this claim comes largely from studies investigating tachyzoite binding, and not SAG1 binding per se. In this study we successfully developed an in vitro attachment assay to directly evaluate the mechanism of SAG1-host cell binding. Compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…16,38 Hence, the characterization of SAG1 immunodominant epitopes and their relations with the ligand-binding site has been a longstanding issue addressed through different approaches. [24][25][26][27][31][32][33]38 The monoclonal antibody used in this study recognizes, in the nanomolar range, the native and recombinant SAG1, and efficiently inhibits SAG1 binding to most of the sera from infected patients that we have tested, suggesting that the mAb 4F11E12 is highly representative of the human anti-Toxoplasma response. Consequently, it is likely that mAb 4F11E12 and human sera recognize overlapping areas on SAG1, a region that is considered to be part of an immunodominant B-cell epitope.…”
Section: Discussionmentioning
confidence: 99%
“…16,38 Hence, the characterization of SAG1 immunodominant epitopes and their relations with the ligand-binding site has been a longstanding issue addressed through different approaches. [24][25][26][27][31][32][33]38 The monoclonal antibody used in this study recognizes, in the nanomolar range, the native and recombinant SAG1, and efficiently inhibits SAG1 binding to most of the sera from infected patients that we have tested, suggesting that the mAb 4F11E12 is highly representative of the human anti-Toxoplasma response. Consequently, it is likely that mAb 4F11E12 and human sera recognize overlapping areas on SAG1, a region that is considered to be part of an immunodominant B-cell epitope.…”
Section: Discussionmentioning
confidence: 99%
“…SRS antigens are thought to facilitate attachment to and invasion of a host cell (6,9,13,18), but the identity of the interacting host cell ligands remains elusive. Recently, X-ray crystallography has revealed that the highly abundant SAG1 specific to the tachyzoite stage forms a homodimer in which the dimeric interface shaped by an extended ␤-sheet forms a deep groove lined with positively charged amino acids (7).…”
mentioning
confidence: 99%
“…Toxoplasma as with other Apicomplexa has an obligatory intracellular developmental stage where it multiplies before bursting from a host cell, pre-adapted to infect other host cells. The ability to invade nearly all nucleated cells in an active multistep process (5-7) is thought to be in part due to several surface proteins, among them the major surface antigen SAG1 (P30), which establishes the first contact between the parasite and the host cell (8,9). As in the case with many other parasitic protozoa (10 -14), glycosylphosphatidylinositol (GPI) 3 -anchored proteins like SAG1 dominate the plasma membrane.…”
mentioning
confidence: 99%